Metal‐Free Stabilization of Monomeric Antimony(I): A Carbene‐Supported Stibinidene. Issue 29 (12th June 2014) - Dorsey, Christopher L.; Mushinski, Ryan M.; Hudnall, Todd W.
Abstract A diamidocarbene was coordinated to an antimony(III) dichloride Lewis acid. Subsequent reduction with magnesium gave a monomeric, formally antimony(I) fragment that is supported by the diamidocarbene. Spectroscopic, crystallographic, and computational analyses demonstrated that the carbene ligand engages the antimony(I) center in π‐backbonding resulting in a short (2.068(7) Å) SbC interaction that is comparable to those observed in known stibaalkenes.